Applications of Biochar for Environmental Safety - Abdelhafez, Ahmed A.; Abbas, Mohammed H. H. (IntechOpen, 2020)
Biochar is a carbon-rich material produced from the pyrolysis of organic materials from agricultural and forestry biomass at a relatively low temperature in the absence of oxygen. As such, it has potential for solving many agricultural and environmental problems.This book is divided into five sections: "Introduction," "Production and Legislation of Biochar," "Applications of Biochar for Soil Fertility Improvement," "Role of Biochar for Soil Remediation and Ameliorating Salinity Effects" and "Applications of Biochar for Water Treatment." Chapters address topics such as the pros and cons of biochar, its production, and its role in remediating and treating contaminated soils and water.